Effect of varying levels of bypass fat on digestibilities of nutrients and balances of N, P and Ca in lactating Jaffrabadi buffaloes - SAVSANI, H H; MURTHY, K S; BHADANIYA, A R; KALARIA, V A; GHODASARA, S N; PATIL, S S (The Indian Journal of Animal Sciences, 2016)
Lactating Jaffrabadi buffaloes (24; first to fourth lactation and average body weight 650.0 kg) were randomly divided into 4 groups of 6 animals each as per completely randomized design and allocated to 4 dietary treatments as T1,T2, T3 and T4. Experimental buffaloes were offered commercial concentrate mixture and cotton seed cake in equal proportion (50:50) to fulfil the protein requirements as per ICAR (1998) along with the basal diet of 10 kg seasonal green and mature pasture grass hay ad lib. Commercial bypass fat was provided to all experimental buffaloes at the rate of 150g per animal for first 15 days prior to parturition and at the rate of 0, 10g, 20g and 30g /kg milk yield in T1, T2, T3 and T4 groups, respectively post partum. DMI, Per cent DMI and DMI/kg W0.75 of lactating buffaloes remained non significant among different treatment groups during entire experiment. Lactating buffaloes also showed non-significant differences in body weight and biometry during different phases of experiment. Differences in water intake (l/day, l/100kg B.W., l/kg W0.75 and l/kg DMI) by different levels of bypass fat supplementation were also non significant. Digestibility of the rations for DM, OM, CP, EE, CF and NFE were not significantly affected by addition of supplemental fat. Nitrogen, phosphorus and calcium balances were positive and non significant among different treatment groups. Plane of nutrition as per ICAR nutritional requirements for Indian buffaloes was comparable among different dietary treatments. Overall results indicates that bypass fat supplementation has positive but non significant effect on nutrient utilization in different groups.